Designing electric braking system for brushless direct current motor as an electric bicycle propulsion - Supriyono, Heru; Supardi, Agus; Romadhon, Muhammad Rafi Nur; Yulianto, Aldi; Utomo, Untung Budi (Institute of Advanced Engineering and Science, 2025)
One of the problems arising in the conversion of pedal-based bicycles into electric bicycles using brushless direct current (BLDC) motors is how to provide an electric braking system for the BLDC motor. Published research on braking systems for electric bicycles from a practical perspective was still limited. The objective of the article is to develop an electric braking system for BLDC motor as a propulsion of electric bicycle converted from pedal-based bicycle from the empirical point of view. The pedal-based bicycle was converted to the electric bicycle by fully replacing its rear wheel including its chain system with the BLDC motor. The braking system was developed by adding a DC motor as a load for BLDC in the braking mode. Test was conducted by turning on the acceleration handle and then the braking action was applied. The stoppage time was recorded from the start of braking action until the wheel was fully stopped. The test results showed that the addition of a direct current (DC) motor as a load can shorten stoppage time of the electric bicycle dramatically, i.e., needs 1.65 seconds compared to 10.14 seconds and 3.09 seconds for without braking and with braking but without DC motor as a load respectively.